Babuta'an Traditional Games In Increasing Students' Learning Motivation - Annisa Hasanah; Zain Ahmad Fauzi; Fahri Fajrul Falah; Norma Paulina; Asyfa Nabila; Linda Rosydah (International Journal of Multilingual Education and Applied Linguistics, 2024)
The researcher chose the traditional game Bubuta'an to overcome noise outside the classroom due to school renovations which resulted in students' lack of focus on learning. The traditional game Bubuta'an is also a traditional game in South Kalimantan which in Indonesian is known as the game Si Buta-Si Buta. The aim of the research is to analyze the role of traditional babuta'an games in increasing students' learning motivation. The type of research used is Classroom Action Research with a qualitative approach. The research results show that the percentage of students' classical learning motivation obtained at the first meeting was 75% with the criterion "Mostly Skilled", at the second meeting it had increased to and had increased at the second meeting to 92% with the criterion " Almost All Skilled" and at the third meeting it had increased to 96% with the criteria "Almost All are Skilled" . This was because at the first meeting several students had not achieved the assessment indicators. So these conditions are below standards set by researchers for developing students' learning motivation. To overcome these obstacles, educators make improvements motivating, providing reinforcement, paying attention and reminding students to be more interested in participating in the learning process. The conclusions obtained by traditional game Babuta'an can be used as a means of developing students' learning motivation.